Human Resource Management in Education: Optimizing Teacher Performance for Better Learning Outcomes - Permatasari, Nirwana; Tandiayuk, Suryadi (Manunggal Halim Jaya, 2023)
Education serves as the cornerstone of national development, and the quality of teaching plays a pivotal role in shaping an exceptional generation. In the dynamic landscape of education, characterized by global shifts and technological advancements, the challenges faced by the sector transcend traditional boundaries. Teachers, as primary conveyors of knowledge, skills, and values, stand at the forefront of this evolving landscape, necessitating optimal performance and adaptability. The attainment of quality education relies on a nuanced understanding and the strategic implementation of Human Resource Management (HRM) practices within the education sector. HRM in education is not confined to mere administrative tasks but represents a strategic imperative that shapes the overall learning experience. From recruitment to professional development, HRM plays a crucial role in equipping educators to meet the evolving demands of the educational landscape. The dynamic interplay between global shifts, the evolving roles of educators, and the imperative for optimal performance underscores the pressing need for a sophisticated approach to HRM in education. This study explores innovative strategies to optimize teacher performance and address unique challenges within education. HR practices, encompassing recruitment, professional development, compensation, and performance management, emerge as essential components for enhancing student outcomes. The effectiveness of HRM strategies is intricately linked to factors such as leadership, organizational culture, and the broader social, political, and economic contexts. An effective HRM system recognizes the dynamic role of teachers, empowering them with current knowledge and skills. The synergy between HRM practices and the quality of human resources acknowledges teachers as dynamic contributors to the learning process. Innovative HRM strategies in education encompass the utilization of technology, personalized professional development, and the promotion of an inclusive work culture. Challenges, ranging from resource shortages to curriculum changes and social factors influencing teacher performance, are thoughtfully addressed. The intricate relationship between HRM and student learning outcomes is investigated, with the aim of achieving alignment between teacher performance and student achievement. The narrative envisions a future where HRM serves as a driving force for educational excellence, fostering an environment that supports growth, innovation, and the quality of learning.